Handbook of mathematical functions with formulas, graphs, and mathematical tables - Abramowitz, Milton, 1915-1958 (U.S. Dept. of Commerce : U.S. G.P.O., 1972)
This book is a compendium of mathematical formulas, tables, and graphs. It contains a table of analytical integrals, differential equations, and numerical series; and includes tables of trigonometric and hyperbolic functions, tables for numerical integration, rules for differentiation and integration, and techniques for point interpolation and function approximation. Additionally, it devotes a entire section to mathematical and physical constants as fractions and powers of Pi, e, and prime numbers; and discusses statistics by presenting combinatorial analysis and probability functions.
Keywords: Functions.; Mathematics -- Tables.; elektronické knihy; electronic books